PELATIHAN SELF ACCEPTANCE MANAGEMENT UNTUK MENINGKATKAN SELF ACCEPTANCE PENDIDIK TERHADAP ANAK BERKEBUTUHAN KHUSUS - muya barida (JURNAL KONSELING GUSJIGANG, 2019)
The process of receiving the condition of Children with Special Needs for educators is not easy. Lack of access to the knowledge, understanding, and skills of educators on the diversity of learners belonging to Children with Special Needs affects the acceptance of different conditions for Children with Special Needs with normal children. Often, educators compare and enforce learners' abilities according to the demands imposed in school. Therefore it is necessary to do training for educators Children with special needs by self-acceptance management. The pretest result shows that the self-acceptance of the educator is moderate. The result of posttest is known that self-acceptance of educator to Children with Special Needs is high. It can be concluded that self-acceptance management training can improve self-acceptance of educators to Children with Special Needs. Training and mentoring of educators of children with special needs can contribute to the implementation of inclusive education in schools, especially in dealing with the diversity of students who are classified as normal or children who have specificity. Ultimately the goal of education to form the optimal human potential can be achieved.